Linguistic and Cultural Peculiarities of Diminutives in Lithuanian Artistic Texts and Their Translation into French Language / Particularités linguistiques et culturelles des diminutifs de la littérature lituanienne, leur traduction en français - Leonavičienė, Aurelija (Kalbotyra, 2015)
The frequent usage of diminutives is a characteristic of the Lithuanian language system. This feature is not common in other languages, for example in French. Lithuanian language has a big potential for the word formation. The Lithuanian language contains approximately 80 suffixes of diminutives which express hypocoristic, ironic, pejorative and other meanings. Meanwhile in French language these meanings are usually expressed by analytical forms together with adjectives such as little, good, etc. or by non-diminutive lexical units. The frequent usage of diminutives conveys lyricism as well as stylistic, sociolinguistic and socio-cultural characteristics of Lithuanian artistic texts. As a result, the diminutives are considered to be an important feature of artistic texts. The aim of this article is to describe diminutives of the Lithuanian language system, to discuss their frequency in the analysed texts, their stylistic value, productivity of the morphemes of diminutives and translation strategies into the French language. The analysis of diminutives translations into the French language during the last 12 years (from 2000 to 2012) allows to define certain tendencies of translation strategies chosen by French translators and to discuss problematic issues of translation. The material for the analysis is composed of novels written by Lithuanian authors (R. Granauskas, R. Gavelis, A. Landsbergis, J. Kunčinas, V. Juknaitė, S. Parulskis, G. Radvilavičiūtė and others) and their translations into the French language that were published in the anthology contemporary Lithuanian novels “Des âmes dans le brouillard” in 2003 and in Lithuanian cultural reviews “Cahiers Lituaniens” published in France in 2000–2012. The investigation is performed by the quantitative, analytical, contrastive linguistic methods. Abstract in French